Early postnatal expression mitigates immune responses to Cas9 in the murine central nervous system - Robert Duba-Kiss; David R. Hampson (Molecular Therapy: Methods & Clinical Development)
A barrier in the development of adeno-associated virus (AAV) gene therapy is the immunogenicity of the AAV particles, and in some cases, the expressed transgene. The immunogenic risk is heightened when exogenous proteins, such as prokaryotic Cas9 nucleases, are used in gene editing. We documented the immune responses generated after CNS injections of AAVs encoding Staphylococcus aureus Cas9 in neonatal vs. adult mice. Injection of AAV-Cas9s containing either a neuron-specific synapsin promoter, or a cytomegalovirus promoter, into neonatal mice resulted in robust expression of Cas9 and activation of microglia. Expression of Cas9 was maintained 3 months post-injection while the microglial response dissipated by this time. In contrast, infusion of AAV-Cas9s into the adult brain resulted in the absence of detectable Cas9 protein and reduced neuronal density. Activation of microglia and astrocytes, T cell infiltration into the CNS, and circulating antibodies were also observed. Surprisingly, these effects were not seen in adult mice administered an AAV encoding EGFP. The lack of detectable Cas9 protein in the adult injected mice indicates that Cas9-expressing neurons were eliminated via a cytotoxic immune response. Our findings suggest that very early postnatal administration may enhance safety and efficacy in treatments for pediatric disorders employing CRISPR-Cas9 gene editing.